HUBUNGAN SELF EFFICACY DAN POLA ASUH OTORITER DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA - Rohmatun, Rohmatun; Taufik, Taufik (Universitas Muhammadiyah Surakarta, 2014)
This research is aimed at investigating the correlation between selfefficacy and authoritarian parenting style toward student s? academic procrastination. The subject of this research is 150 students of faculty of of Psychology, Medicine, and Economy of Sultan Agung Islamic University who are working on the final project. The major hypothesis proposed in the research is that there is a correlation between self-efficacy and authoritarian parenting style with students? academic procrastination. The minor hypotheses are as follows: (1) there is a negative correlation between self-efficacy with academic procrastination; and (2) there is a positive correlation between authoritarian parenting style with academic procrastination. This research used three of scale for the data collection namely academic procrastination scale, self-efficacy scale and authoritarian parenting stale scale. The statistic analysis used in the research is regression to test major hypothesis and the parsial analysis to test minor hypothesis. The research results show that (1) there is correlation between self-efficacy and authoritarian pareting style with students? academic procrastination; (2) there is a significant negative correla tion between self-efficacy with academic procrastination toward college students; and (3) there is a significant positive correlation between authoritarian parenting style with academic procrastination toward college sudents.